2009
DOI: 10.1037/a0012652
|View full text |Cite
|
Sign up to set email alerts
|

Decreased family accommodation associated with improved therapy outcome in pediatric obsessive–compulsive disorder.

Abstract: Pediatric obsessive-compulsive disorder (OCD) is a chronic, disabling condition that affects both patients and their families. Despite the identification of efficacious treatments (e.g., cognitivebehavioral therapy and selective serotonin reuptake inhibitor medications), not all patients respond fully. The purpose of the present study was to examine whether the amount of family accommodation provided to pediatric OCD patients is associated with treatment outcome, and whether decreases in accommodation are asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
157
1
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(177 citation statements)
references
References 18 publications
10
157
1
9
Order By: Relevance
“…There was some indication that family factors (family accommodation) were associated with treatment outcome in the present study and this is consistent with findings of other anxiety intervention studies in ASD 5 and outcome in general pediatric OCD treatment studies 40 . Group and individual psychological interventions for anxiety disorders in this group should then seek the engagement of relevant care-giving/supportive individuals in treatment.…”
Section: Demographics and Clinical Featuressupporting
confidence: 81%
“…There was some indication that family factors (family accommodation) were associated with treatment outcome in the present study and this is consistent with findings of other anxiety intervention studies in ASD 5 and outcome in general pediatric OCD treatment studies 40 . Group and individual psychological interventions for anxiety disorders in this group should then seek the engagement of relevant care-giving/supportive individuals in treatment.…”
Section: Demographics and Clinical Featuressupporting
confidence: 81%
“…Instead, exposure therapies should be selected over EMDR for youth populations. Other treatments that focus on supportive listening or nondirective approaches only instead of directly addressing the client's fears (e.g., client-centered therapy, relationship counseling) have also been tested and have failed to meet criteria for Levels 1-4, perhaps because these treatments inadvertently work to ''accommodate'' anxiety, which has been shown to predict anxiety severity and treatment outcomes (e.g., Merlo, Lehmkuhl, Geffken, & Storch, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…However, Merlo, Lehmkuhl, Geffken & Storch (2009) showed that reductions in family accommodation, achieved through family-based cognitive-behavioural therapy, were associated with positive response to treatment in the affected relative.…”
Section: Introductionmentioning
confidence: 99%